Long-term anxiety of natural and biological hazards on community and healthcare workers - Chen, Po-Fei; Lung, Hsuan; Chang, Mei-Chung; Lung, For-Wey (Frontiers in Psychiatry, 2025)
BackgroundExposure to natural and biological hazards has been linked to long-term declines in mental health. However, limited research has examined the sustained psychological impact of these disasters over extended follow-up periods.MethodsThis study investigated the long-term mental health consequences of natural and biological hazards among healthcare workers and community residents through three longitudinal datasets collected over two decades. Data sources included: (1) 127 healthcare workers exposed to Severe Acute Respiratory Syndrome (SARS) in 2003, with 123 followed up one year later; (2) 152 community residents affected by Typhoon Morakot in 2009, with 125 followed up 1.5 years later; and (3) 458 healthcare workers affected by Coronavirus disease 2019 (COVID-19) in 2020, with 321 followed up two years later.ResultsFindings show that mental distress prevalence among community residents remained stable (1.6% initially vs. 1.5% at follow-up), whereas healthcare workers exhibited increasing distress over time (SARS: 4.7% to 15.4%; COVID-19: 9.7% to 11.8%). Pathway modeling revealed that initial anxiety at the onset of SARS, Typhoon Morakot, and COVID-19 was a strong predictor of long-term psychological distress.ConclusionsThese results highlight the importance of sustained mental health interventions for healthcare workers facing prolonged exposure to stressors during biological disasters. In addition to early anxiety screening, system-level measures such as adequate staffing, transparent communication, and institutional preparedness are essential to mitigate long-term psychological consequences.